Penerapan Model Pembelajaran Interaktif dengan Media Miniatur Untuk Peningkatan Hasil Belajar IPA Sekolah Dasar - Bayu Widiyanto (Bidayatuna, 2020)
Science is a subject that studies the cause and effect of events that occur in nature, science learning involves students playing an active role in finding concepts. So that we need a learning model and learning media that can make it easier for students to find a concept. Miniature media is a learning medium that can be used in learning for students to understand concepts. This study aims to determine the increase in student learning outcomes by using an interactive learning model about grouping of animals. This research is a classroom action research using the Kemmis & Mc Taggart model. In this study, measurements were made with student activity sheets and within a certain time students were given a posttest. The subjects of this study were third grade students of SDN Kemuning Lor 02 Jember